Of Scapegoats and Signals: Investor Reactions to CEO Succession in the Aftermath of Wrongdoing. (September 2016) - Gangloff, K. Ashley; Connelly, Brian L.; Shook, Christopher L.
If an organization's management is caught in the act of misconduct, it may call for a changing of the guard. Surprisingly, though, there is little empirical evidence examining the presumed benefits of executive turnover in the aftermath of wrongdoing. In this study, we explore investor reactions to CEO turnover following financial misrepresentation. We theorize and find that firms can be successful at managing investor reactions to organizational misconduct by either scapegoating or signaling change, but middle-ground approaches that do not commit to one or the other are less successful. We test our ideas in a firm-level event study of market reactions to CEO successions following a material financial statement restatement. We discuss the results, which generally support our predictions, and their implications for development of the scapegoating and signaling literatures and research on both executive succession and restoring corrupt organizations.